(untitled) (Perner’s Contacts, 2020)
The paper analyses windmill power turbines (WT) effects on ground-based radar functions, used for air traffic control. The primary radars, especially surveillance, landing and tracking systems for frequency ranges 1 GHz up to 10 GHz, are considered. The paper is dealing with the estimations of radar cross sections (RCS) considering typical shapes and dimensions of windmill turbines and with shadowing due to an individual WT and groups of power stations for primary and secondary radars. As the given problems are usually very complicated, and numerical simulations are extremely demanding from viewpoint of time and memories, the simplified equations are given allowing the basic preliminary analyses